Mental imagery and emotion in treatment across disorders: using the example of depression. - Holmes, E; Lang, T; Deeprose, C (2009)
Abnormalities in mental imagery have been implicated in a range of mental health conditions. Imagery has a particularly powerful effect on emotion and as such plays a particularly important role in emotional disorders. In depression, not only is the occurrence of intrusive negative imagery problematic, but also the lack of positive (in particular, future-directed) imagery is important. The authors suggest that, in depression, imagery can exacerbate the effects of interpretation bias. This article outlines an experimental psychopathology subcomponents model of depression that focuses specifically on the role of imagery and interpretation bias in the maintenance of the disorder. The authors propose that negative intrusive imagery, a lack of positive imagery, and negative interpretation bias serve both independently and interactively to maintain depressed mood. Finally, the authors consider the implications of this imagery-based approach for the development of new cognitive treatments in this area.